Estimated changes of drought tendency in the Carpathian Basin - Sábitz, Judit; Pongrácz, Rita; Bartholy, Judit (Hungarian Geographical Bulletin, 2014)
Drought conditions are often characterized by various drought indices. In this paper different types of indices (i.e. standardized precipitation anomaly index, SAI, Thornthwaites aridity index, TAI, and Peds drought index, PDI) are used to estimate the future changes in drought conditions in the Carpathian Basin. For this purpose 25 km horizontal resolution gridded outputs of several regional climate models are used from the project ENSEMBLES covering the period 19512100 and taking into account the A1B emissions scenario. The results suggest remarkable drying in the region, especially, in summer, which emphasize the importance of developing appropriate adaptation strategies addressing this issue.